Influence of Team Ability on Physical and Tactical Performance According to Playing Position in Spanish Soccer LaLiga. - Carlos Lago; Ezequiel Rey; Roberto López del Campo; Ricardo Resta; Yixiong Cui; Miguel Ángel Gómez Ruano (European Journal of Human Movement)
The current manuscript aims to verify if the team ability and the players' age influence the distance covered at various speeds and the technical-tactical performance in elite soccer. Physical and technical performance data from all matches in the Spanish LaLiga during the 2018–2019 season were analysed using a computerised tracking system (TRACAB, Chyronhego, New York, USA). Players were categorized into five positional roles: Central Defenders (CD; match observations = 1,179), fullbacks (FB; match observations = 980), Central Midfielders (CM; match observations = 1,000), External Midfielders (EM; match observations = 440), and forwards (F; match observations = 412). The following variables were considered: total distance covered (TD) covered by players, distance covered at high intensity (HIR; >24.0 km · h−1),  number of efforts made at high-intensity running (N of HIR), Average Speed (AvSpeed, km · h−1), Offensive Volume (Off Vol): sum of passes, shots, and dribbles executed by the player; Defensive Volume (Def Vol): sum of recoveries, clearances, opponent attack interruptions, and blocked shots executed by the player; and (iii) Game Volume (Game Vol): sum of offensive actions and defensive actions. The variable team quality was established by running an automatic clustering model (two-step) that identified 4 groups of teams: Best teams (ranked from 1st to 6th position), intermediate-higher ranked (from 7th to 11th position), intermediate-lower ranked (from 12th to 15th position), and lower ranked teams (from 16th to 20th position). Generalized linear models were used to analyse differences in players’ match performance according to the team quality, age, and playing position. The main results revealed that: (i) Overall, the team quality affected the performance in all variables (all p<0.001). Players from best-ranked teams outperformed the ones from intermediate or low-ranked teams in all variables (p<0.05). (ii) However, this effect varied by playing position. (iii) Younger players demonstrated better physical performance compared to older players, especially among FB and CM.